(untitled) (Journal of Environmental Science and Natural Resources, 2015)
The experiment was conducted to develop preserve and candy from fresh unripe bel fruit and studied their storage life. The preserve was made from 60%, 65% and 70% sugar concentration. The candies were made from 65%, 70% and 75% sugar concentration. Among them the best preserve and candy was identified on the basis of overall acceptability. The study showed that the color, flavor, texture and overall acceptability among the preserves and among the candies were different . The preserve (PE70) made from 70% and the candy (CY75) made from 75% sugar concentration was best among others of the similar product. Higher concentration of sugar and slower processing gives higher acceptability for preserve and candy. Among different changes, moisture concentration was prominent during preparation of preserve and candy. The moisture content was 32.5% and 27% for preserve and candy respectively which were nearly half of the initial concentration of fresh unripe bel fruit. The storage st ability of candy (120 days) was slightly higher than the storage stability of preserve (90 days). DOI: http://dx.doi.org/10.3329/jesnr.v6i2.22108 J. Environ. Sci. & Natural Resources, 6(2): 121-126 2013